The Effect of the Problem-Based Learning Model on Creativity and Collaboration Skills in Science Learning among Fifth-Grade Students of SD Negeri 4 Palu - Nafis Nurvita Kasyanto; Azizah Azizah; Asriani Asriani; Sry Wahyuni (Journal of General Education and Humanities, 2026)
This study was conducted to address the low levels of creativity and collaboration skills among fifth-grade students at SD Negeri 4 Palu, which were attributed to the use of conventional teaching practices. The objective of this research was to examine the effect of the Problem-Based Learning (PBL) instructional model on students' creativity and collaboration skills in science learning. The study employed a pre-experimental design with a one-group pretest–posttest. The research subjects were 16 fifth-grade students selected through saturated sampling. Data were collected through questionnaires, observations, and documentation, and analyzed using a Paired-Samples T-Test in SPSS version 30. The results revealed a significant increase in students' creativity scores, with the mean rising from 19.38 in the pretest to 28.69 in the posttest. Similarly, the mean collaboration score increased from 21.13 to 31.88. Hypothesis testing showed a significance value of less than 0.001 (Sig. < 0.05), indicating that the Problem-Based Learning model had a statistically significant effect on improving students' creativity and collaboration skills. These findings suggest that implementing PBL effectively enhances essential 21st-century skills in elementary science learning.